Plant communities and potential phytoremediation species for resource utilization of abandoned drilling mud - Wang, Shuzhuan; Hao, Mingde (Frontiers in Environmental Science, 2024)
Oil and gas development produces a large amount of abandoned drilling mud, which may be a source of pollution but may also be a potential resource. A quadrat sampling method was used in the Changqing Oilfield to investigate the plant community characteristics inside and outside abandoned drilling mud pits at different completion times. The importance value of plant showed that the natural succession of plant communities in the abandoned drilling mud pool could be divided into three stages: (1) 4-8 years after the completion of the well, Leymus secalinus, Calamagrostis epigeios with the importance values of more than 100, were dominant species in the initial construction stage; (2) 9-13 years after the succession, the intense competition stage of the plant community, although the importance value of plant inside the mud pit had decreased, it was still higher than the importance value of plant outside the mud pool. The importance values of Leymus secalinus and Artemisia scoparia outside the mud pool were 62.5 and 52.5, while those in the mud pool were 95 and 75, respectively; (3) 23-28 years after the succession, the gradual stabilization stage of the plant community, the importance value of plant was lower than that in the mud pool. Leymus secalinus, Calamagrostis epigeios and Artemisia scoparia could be used for phytoremediation of abandoned drilling soil for their higher importance values. Changes of Shannon-Wiener index, Pielou index, Community ecological dominance and vegetation biomass showed that the mud pit was suitable for the recovery and growth of the dominant species, improved the diversity of plant communities inside the mud pit compared with the stable plant community outside the mud pit. Abandoned drilling mud increased the content of nitrogen, potassium and trace elements in plants. While the variation coefficient of heavy metal content in plants inside and outside the mud pit was large, but the content of heavy metals in plants was within the normal range. Abandoned drilling mud has the potential for resource utilization on the premise of ensuring soil quality and safety. This study provides information on the resource utilization, and environmental safety of abandoned drilling mud.